2018
DOI: 10.22441/mix.2018.v8i3.011
|View full text |Cite
|
Sign up to set email alerts
|

Efisiensi Perusahaan Konstruksi Di Indonesia

Abstract: Along with the increase in government programs to accelerate infrastructure development, the construction industry in Indonesia has faced intense competition which has forced construction companies in Indonesia to be efficient in order to remain profitable.  This study is aimed to measure the efficiency of construction companies in Indonesia.  Data Envelopment Analysis (DEA)is used for the research method and data is obtained from the companies’ yearly report in the period 2010-2016 listed in the Indonesia Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…The financial crisis in 1998 taught a lesson that the banking sector is very influential on the national economy (Baroroh, 2012); (Amah, 2013); (Aprianingsih, & Yushita, 2016); (Suci, 2017). An Efficiency is the ability that must be possessed by banks to be able to face increasingly intense competition (Melani & Suwarni, 2013); (Malik, 2017); (Sukandar, et, al., 2018). Because banks are complex entities, ratio analysis is not enough to describe the real bank's financing.…”
Section: Introductionmentioning
confidence: 99%
“…The financial crisis in 1998 taught a lesson that the banking sector is very influential on the national economy (Baroroh, 2012); (Amah, 2013); (Aprianingsih, & Yushita, 2016); (Suci, 2017). An Efficiency is the ability that must be possessed by banks to be able to face increasingly intense competition (Melani & Suwarni, 2013); (Malik, 2017); (Sukandar, et, al., 2018). Because banks are complex entities, ratio analysis is not enough to describe the real bank's financing.…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai bagian dari hukum konstruksi, perjanjian konstruksi memiliki peran penting dalam mengatur hubungan antara pemilik proyek dan kontraktor. Penelitian oleh (Sukandar et al, 2018) mengeksplorasi aspek-aspek kunci yang harus dipertimbangkan dalam perjanjian konstruksi, termasuk ketentuan pembayaran, jadwal proyek, dan penyelesaian sengketa.…”
Section: Hukum Konstruksiunclassified
“…However, has implemented management that has been made by companies ranging from three to 10 years. The development of the construction industry in Indonesia had developed quite rapidly [32]. In 2013, it was reported that Indonesia had a construction business entity of 131080 so that the Indonesian construction market was one of the largest in Southeast Asia.…”
Section: Company Profilementioning
confidence: 99%
“…Applying lean concepts in the construction industry should identify what variables can cause inefficiencies in construction projects. Alwi et al [32] sort categories from waste into five parts, namely repair, waiting periods, material, human resource, and operation. Each section has several important points, which are often the cause of ineffective construction project work.…”
Section: Waste Causes Variablesmentioning
confidence: 99%